Building Skills in the Digital Age through Merdeka Belajar Curriculum Development Training - Lailiyah, Nur; Pitoyo, Andri; Sujarwoko, Sujarwoko; Rahmayantis, Marista Dwi; Waryanti, Endang; Sasongko, Sempu Dwi; Sardjono, Sardjono; Puspitoningrum, Encil; Muarifin, Moch.; Gigik, Yolanda Rensia; Putri, Fadila Ardinaning (CV. Srikandi Kreatif Nusantara in collaboration with Institut Teknologi Mojosari Nganjuk, 2024)
The swift progress of digital technology necessitates an educational overhaul to equip the younger generation for 21st-century challenges. The Merdeka Belajar curriculum, a government initiative, aims to enhance education quality and foster skills pertinent to contemporary demands. This community service endeavor empowers teachers in Karangrejo village to develop Merdeka Belajar curriculum infused with digital skills. The training, involving teachers from three elementary schools, focuses on comprehending the curriculum's principles and crafting lesson plans integrating digital competencies like data literacy, programming, and media skills. Employing a participatory approach, the program merges lecture sessions, group discussions, and lesson plan development exercises. Participants gain access to digital resources and online platforms to aid curriculum implementation. Results reveal heightened comprehension of the curriculum and the significance of digital skills integration. Teachers successfully devise innovative, contextually relevant lesson plans employing digital tools to augment student engagement and motivation. This community service initiative significantly contributes to nurturing digital era proficiencies through Merdeka Belajar Curriculum development training. Enhanced teacher abilities in digital skills integration aim to prepare students as adept individuals poised to confront future challenges.